The Influence of Earnings Management and Earnings Opacity on Firm Value with Corporate Governance Mechanism as a Moderating - Hendriyana Hendriyana; Etty Murwaningsari (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study investigates the impact of Earnings Management and Earnings Opacity on Firm Value, with Corporate Governance as a moderating factor. Firm Leverage and Firm Size are utilized as control variables to refine the analysis. The research comprises 304 observations from 76 consumer goods and agriculture companies listed on the Indonesia Stock Exchange between 2018 and 2021. Panel data regression analysis is conducted to test the hypotheses. Results reveal that Earnings Management and Earnings Opacity positively influence Firm Value. However, Corporate Governance does not enhance the relationship between Earnings Management and Firm Value. In contrast, Corporate Governance amplifies the impact of Earnings Opacity on Firm Value, underscoring the critical role of governance in mitigating the adverse effects of financial report opacity. This study enriches existing literature by examining the differential moderating effects of Corporate Governance on Earnings Management and Earnings Opacity. The findings offer valuable insights for corporate leaders, highlighting that robust governance and financial transparency drive sustainable performance and bolster investor confidence. By fostering transparency and accountability, companies contribute to market stability and public trust, especially in sectors vital to economic growth. Targeting specific sectors in emerging markets advances the understanding of financial reporting and governance dynamics.